Wives’ Sexual Rights: Shāfiʿī Fiqh Norms and Indonesian Positive Law - Mujahid, Ilham; Nurrohman, Nurrohman; Burhanuddin, Burhanuddin; Rasyid, Fauzan Ali; Fawzi, Ramdan (Jurnal Hukum IUS QUIA IUSTUM, 2026)
Wives’ sexual rights in marriage constitute a fundamental aspect of human dignity that remains problematic in the construction of classical Islamic jurisprudence and Islamic family law in Indonesia. In the Shāfiʿī school of fiqh, particularly as reflected in al-Muhadzdzab by Abū Isḥāq al-Shīrāzī, sexual intercourse (jimāʿ) is predominantly positioned as a prerogative right of husbands, while wives’ sexual rights are neither explicitly articulated nor recognized as equal. In contrast, the Indonesian positive law through the Marriage Law, the Compilation of Islamic Law (KHI), the Law on Elimination of Domestic Violence, and the Law on Sexual Violence Crimes demonstrates a more progressive orientation by acknowledging wives’ sexual rights as an integral component of the protection of human dignity and human rights. This study employed a normative legal approach with a content analysis of Shāfiʿī fiqh texts and a comparative analysis of the Indonesian positive law regulations. The findings revealed a normative gap between hierarchical classical fiqh and positive law that was oriented toward equality and the protection of women’s bodily rights. The primary contribution of this article is found in its direct dialectical engagement between the Shāfiʿī fiqh norms and the Indonesian positive law, followed by a proposed reinterpretation of fiqh grounded in maqāṣid al-sharīʿah, which affirms wives’ sexual rights as a reciprocal right in marriage. Furthermore, this article improves a concrete legal formulation by proposing a conceptual revision of nafkah bāṭin (intimate maintenance) in the Compilation of Islamic Law to encompass the proper fulfillment of wives’ biological needs which are free from coercion and accompanied by clear legal consequences. Therefore, this study enriches the discourse on Islamic family law while offering a normative bridge between fiqh authority and the Indonesian positive law grounded in gender justice.